Critical appraisal of the instantaneous end‐diastolic pulmonary arterial wedge pressures. (6th October 2020) - Manouras, Aristomenis; Lund, Lars H.; Gellér, László; Nagy, Anikó Ilona; Johnson, Jonas
Abstract: Aims: A substantial shift in the field of pulmonary hypertension (PH) is ongoing, as the previous practice of mean pulmonary arterial wedge pressure (PAWPM ) is no longer supported. Instead, aiming for a better estimate of end‐diastolic pressures (EDP), instantaneous PAWP at mid‐A‐wave (PAWPmid‐A ) or, in the absence of an A‐wave, at 130–160 ms following QRS onset has recently been recommended. Electrocardiogram‐gated PAWP (PAWPQRS ) has also been proposed. The quantitative differences as well as the diagnostic and prognostic utility of these novel PAWP measurements have not been evaluated. We set out to address these issues. Methods and results: Pressure tracings of 141 patients with PH due to left heart disease (PH‐LHD) and 43 with primary pulmonary arterial hypertension (PAH) were analysed. PAWP was measured as follows: (i) mean pressure (PAWPM ); (ii) per the latest consensus approach [PAWPmid‐A, or in atrial fibrillation 130, 140, 150, and 160 ms following QRS onset (PAWP130–160 )]; (iii) at QRS onset (PAWPQRS ); and (iv) Z‐point (PAWPZ ). For each PAWP, the corresponding pulmonary vascular resistance (PVR) and diastolic pressure gradient were calculated. The cohort comprised 45% female. Mean age was 66 ± 15. PAWPmid‐A was in good agreement with PAWPZ (17.3 [14.5 to 21.2] vs. 17.6 [14.2 to 21.6] mmHg, P = 0.63), whereas PAWPQRS provided significantly lower values (15.3 [12.5 to 19.2] mmHg, P < 0.001). In atrial fibrillation, PAWP130 and PAWPQRS yielded the optimal temporal and quantitative analyses of EDPs. The ability to differentiate PAH from PH‐LHD was similar for the various PAWP measurements [PAWPM : area under the curve (AUC) 0.98, confidence interval (CI) 0.96–0.99; PAWPmid‐A/130 : AUC 0.94, CI 0.91–0.98; PAWPQRS : AUC 0.96, CI 0.94–0.99, P < 0.001 for all]. PVR based on instantaneous PAWP measurements failed to provide superior prognostic information in PH‐LHD as compared with conventional PVR. Conclusions: Although instantaneous PAWP measurement might better represent EDP, they nevertheless fail to yield incremental diagnostic or prognostic information in PH‐LHD as compared with conventional measurements.